2009
DOI: 10.1002/qua.22038
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectrum of 2‐pyridone+: Ab initio and time‐dependent density functional calculations

Abstract: In a comparative study, the doublet and quartet electronic states of the 2-pyridone ϩ cation are calculated using the PBE0/6-311ϩG(d,p) technique and the CASSCF and MRCI(ϩQ) methods in connection with the cc-pVDZ and cc-pVTZ Dunning's basis sets. Our data show that TD-DFT describes quite well the vertical excitation energies of these electronic states, whereas, multiconfiguration methods should be used for the investigation of the fragmentation and the dynamics of this molecular species. This is related to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
3
10
0
Order By: Relevance
“…Table IV shows that PBE0 vertical excitation energies are smaller than those computed using multireference methods. This trend was already pointed out in benchmark calculations made on similar medium‐size systems42. No evident basis set effect is noticeable when we compare the data derived by aug‐ cc ‐pVDZ(‐PP) and aug‐ cc ‐pVTZ(‐PP).…”
Section: Resultssupporting
confidence: 76%
“…Table IV shows that PBE0 vertical excitation energies are smaller than those computed using multireference methods. This trend was already pointed out in benchmark calculations made on similar medium‐size systems42. No evident basis set effect is noticeable when we compare the data derived by aug‐ cc ‐pVDZ(‐PP) and aug‐ cc ‐pVTZ(‐PP).…”
Section: Resultssupporting
confidence: 76%
“…In cases where the corresponding electronic wavefunctions are dominantly described by a unique determinant, time-dependent density functional theory (TD-DFT) [105,106], equation-of-motion coupled clusters (EOM-CC), and third-order algebraic-diagrammatic construction approximation scheme (ADC(3)) for the one particle Green's function [107][108][109] all represent good approximations. Through a comparative study of the lowest electronic states of the 2-pyridone + cation (a NAB analog) using PBE0/6-311 + G(d,p) and CASSCF/MRCI/cc-pVDZ, Hammoutène et al [94] showed that both TD-DFT and CASSCF/MRCI describe correctly the vertical excitation energies of these electronic states, whereas one should use multiconfiguration methods for mapping the evolution of the potential energy surfaces far from the molecular region and for treating the unimolecular decomposition processes undertaken by the 2-pyridone + cation. This is due to the possible change of the nature of the wavefunctions of these electronic states along the corresponding reactive coordinates not accounted for by TD-DFT methods.…”
Section: Theoretical Methods For the Analysis Of Photoionization And mentioning
confidence: 99%
“…Scheme 3), and their dimers together represent a model system to study NABs, isolated or paired, as well as the hydrogen bonding in their complexes. The neutral species were widely studied experimentally and theoretically as detailed in [9,94]. Mainly, the work published in these references accurately characterized the equilibrium structure of both tautomers, their relative energies, and their electronic excited states.…”
Section: -Pyridonementioning
confidence: 99%
“…29 Very recently, of the authors of the present paper published a theoretical study of the electronic structure of [2-pyridone] + using ab initio and TD-DFT methodologies. 30 They showed that TD-DFT methods describe accurately the vertical excitation energies of the lowest [2-pyridone] + electronic states, whereas one must choose multiconfiguration (e.g. CASSCF or MRCI(+Q)) methods to study the dynamics and fragmentation of this cation.…”
Section: Introductionmentioning
confidence: 99%
“…CASSCF or MRCI(+Q)) methods to study the dynamics and fragmentation of this cation. In a separate paper, 31 similar calculations on the [2-hydroxypyridine] + singly-charged ion were presented together with the anharmonic wavenumbers of both cationic tautomers computed at the PBE0/6-311+G(d,p) level of theory. Here, we investigate the gas-phase singlephoton photoionization of 2-pyridone and its tautomer produced in a jet-cooled molecular beam.…”
Section: Introductionmentioning
confidence: 99%